(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This text presents the Observatory of Artistic Practices in Prisons and Other Spaces of Deprivation of Liberty, created in 2020 by educators, artists, researchers, and students working in prisons and juvenile detention facilities. Grounded in an abolitionist perspective, the Observatory brings together experiences with the aim of mapping, documenting, and promoting the exchange of methodologies. The article contextualizes the prison system and structural racism, describes artistic initiatives carried out in different institutions, international exchange experiences, actions developed during the COVID-19 pandemic, and projects aimed at specific populations, including women and LGBTQIAPN+ individuals. It argues for art as a form of resistance, critical education, and radical imagination in opposition to punitive carceral logic.